Động đất Đô Lương, Nghệ An ngày 7/1 và ngày 12/1 năm 2015 - Sơn, Lê Tử; Chinh, Vũ Văn; Thủy, Nguyễn Ngọc; Dũng, Nguyễn Quốc; Yêm, Nguyễn Văn; Xuyên, Nguyễn Đình; Cường, Nguyễn Quốc; Hùng, Nguyễn Tiến; Minh, Nguyễn Lê (Vietnam Journal of Earth Sciences, 2018)
The Do Luong...